An Action Research and Multiple Case Study:Fostering Early Childhood Language Development - Anggraeni, Netty; Putriyanti, Lina; Sulianto, Joko (Universitas Padjadjaran, 2025)
Language development in early childhood is a fundamental foundation for the formation of thinking, communication, and social skills. This research aims to explore in-depth and develop effective strategies for stimulating early childhood language development, as well as to identify challenges and solutions through the implementation of Action Research in two Early Childhood Education (ECE) institutions in Bandung City. This study adopts a qualitative approach with a dual case study design combined with Action Research. The study was conducted at PAUD Rumah Bintang and PAUD Alamanda, Bandung City, involving teachers, students, and principals as subjects. The Action Research design was applied in two cycles, encompassing planning, implementation, observation, and reflection, to develop and evaluate the effectiveness of strategies directly in the field. Data collection involved participatory observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles and Huberman with triangulation techniques for data validity. The research findings indicate that the implementation of Action Research successfully optimized diverse language stimulation strategies, including read-aloud practices and interactive conversations, adapted to the unique context of each ECE institution. Another key finding is the adaptive strategies in addressing challenges such as limited resources and children's diverse language backgrounds, with solutions emerging from the cycle of reflection and field-based improvement. This study recommends the Action Research approach as an effective framework for ECE educators and institutions to continuously develop and tailor language learning strategies. Keywords: Action research, childdDevelopment, early childhood, language development, learning strategies.